Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1159/000524745
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Photodynamic Therapy with Fractionated 5-Aminolevulinic Acid 20% versus Conventional Two-Stage Topical Methyl Aminolevulinate for Superficial Basal-Cell Carcinoma

Abstract: <b><i>Background:</i></b> Photodynamic therapy (PDT) is a noninvasive treatment for patients with superficial basal-cell carcinoma (sBCC). The efficacy of PDT may vary with different photosensitizers and treatment schedules. <b><i>Objective:</i></b> Our objective was to evaluate whether fractionated 5-aminolevulinic acid 20% (ALA)-PDT is superior to conventional two-stage methyl aminolevulinate (MAL)-PDT for sBCC. <b><i>Methods:</i></b> We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…For inclusion, histological confirmation of the BCC was required in all studies [ 33 47 , 49 ] except for one which this was not reported [ 48 ]. As presented in table 1 , for the assessment of response to treatment, clinical evaluation was the main method with histological confirmation to be utilized only in cases of residual or recurrent lesions [ 33 , 34 , 36 42 ]. Some trials used clinical evaluation alone [ 43 45 , 47 ] or clinical and histological together [ 35 , 46 ] for the confirmation of treatment response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For inclusion, histological confirmation of the BCC was required in all studies [ 33 47 , 49 ] except for one which this was not reported [ 48 ]. As presented in table 1 , for the assessment of response to treatment, clinical evaluation was the main method with histological confirmation to be utilized only in cases of residual or recurrent lesions [ 33 , 34 , 36 42 ]. Some trials used clinical evaluation alone [ 43 45 , 47 ] or clinical and histological together [ 35 , 46 ] for the confirmation of treatment response.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, data from another study exhibited lower recurrence rates at 5 years of follow-up after conventional two-stage MAL-PDT compared to fractionated ALA-PDT, although no significant risk of treatment failure was observed in the first 3 years. For both interventions the aesthetic results were rated as good-to-excellent for more than 90% of patients [ 33 , 34 ]. Salimvuory et al compared MAL-PDT, ALA-PDT and hexaminolevulinate (HAL)-PDT and showed no differences in the efficacy and safety between the arms but with a short duration of follow-up at 3 months [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, MAL therapy was proven to be more effective than ALA. It is worth to say that the cosmetic outcome was similar in both therapies (82). However, another study that compares the histological clearance, tolerability and cosmetic outcome of MAL, BF-200 ALA, and lowconcentration Hexyl aminolevulinate (HAL) in the PDT of non aggressive BCC.…”
Section: -Alamentioning
confidence: 99%
“…promising short-term complete response rates of up to 80%-95% [15,29]. However, a recent study on the long-term efficacy of fractionated ALA-PDT versus conventional double MAL-PDT showed fractionated PDT to be less effective [30].…”
Section: Plos Onementioning
confidence: 99%